A Review on the Utilization of Guarded Hot Plate Apparatus for Obtaining Thermal Conductivity - Singh, Sarabjit; Singh, Navdeep; Saini, Aastitva (Journal of Advanced Research in Mechanical Engineering and Technology, 2020)
The current paper addresses a brief overview of various works carried out to obtain the thermal conductivity of engineering materials by using a guarded hot plate apparatus. There are various types of operators for measurement of thermal conductivities and are available in different designs and varied ranges of thermal conductivities and temperatures. Guarded hot plate apparatus is one of the apparatus which is successfully employed for measurement of thermal conductivity in which there is a heating plate sandwich in the middle of the material that is heating plate will remain in the middle of a material having same directions and the material is kept on its top and bottom side. The underlying principle of this apparatus is Fourier’s Law of heat conduction. Overall it was observed and depicted that various researches have used this apparatus as it is capable of measuring the thermal conductivity of a wide range of materials like insulators having very low thermal conductivity and good conductors having very high thermal conductivity values. How to cite this article: Singh S, Singh N, Saini A. A Review on the Utilization of Guarded Hot Plate Apparatus for Obtaining Thermal Conductivity. J Adv Res Mech Engi Tech 2020; 7(1&2): 26-29. DOI: https://doi.org/10.24321/2454.8650.202002